3D Silk Fiber Construct Embedded Dual-Layer PEG Hydrogel for Articular Cartilage Repair – In vitro Assessment - Kim, Jung Soo; Choi, Jaeho; Ki, Chang Seok; Lee, Ki Hoon (Frontiers in Bioengineering and Biotechnology, 2021)
Since articular cartilage does not regenerate itself, researches are underway to heal damaged articular cartilage by applying biomaterials such as a hydrogel. In this study, we have constructed a dual-layer composite hydrogel mimicking the layered structure of articular cartilage. The top layer consists of a high-density PEG hydrogel prepared with 8-arm PEG and PEG diacrylate using thiol-norbornene photo-click chemistry. The compressive modulus of the top layer was 700.1 kPa. The bottom layer consists of a low-density PEG hydrogel reinforced with a 3D silk fiber construct. The low-density PEG hydrogel was prepared with 4-arm PEG using the same cross-linking chemistry, and the compressive modulus was 13.2 kPa. Silk fiber was chosen based on the strong interfacial bonding with the low-density PEG hydrogel. The 3D silk fiber construct was fabricated by moving the silk fiber around the piles using a pile frame, and the compressive modulus of the 3D silk fiber construct was 567 kPa. The two layers were joined through a covalent bond which endowed sufficient stability against repeated torsions. The final 3D silk fiber construct embedded dual-layer PEG hydrogel had a compressive modulus of 744 kPa. Chondrogenic markers confirmed the chondrogenic differentiation of human mesenchymal stem cells encapsulated in the bottom layer.